Access to justice for reproductive and sexual health rights of women through law faculty clinics (2015)
Reproductive and sexual health issues affecting women and girls include sexual abuse, rape, coercion, harassment, sexually-transmitted infections, unsafe sex, unwanted pregnancy and illegal abortion, infertility and inability to regulate fertility or negotiate sex. These are most often considered private and confidential, and victims may not desire or require the formalities and exposure of regular courts. The pro-bono legal clinics without resort to the regular courts or litigation, particularly in the resolution of issues affecting women’s reproductive and sexual health rights, is another form of access to justice. The employment of a plural normative system of resolving dispute in African lives and society remains crucial to engendering and ensuring access to justice for women. This paper discusses the concept of access to justice for women in matters affecting their reproductive and sexual health rights. It espouses the role and strategies employed by the Women’s Law Clinic, University of Ibadan in ensuring access to justice for indigent women in Ibadan area of Oyo State of Nigeria whose reproductive and sexual health rights have been violated or threatened. It concludes on the premise that access to justice against violations of reproductive and sexual health rights starts with the initiation of processes for recognition and awareness of these rights. The paper also discusses factors affecting access to justice and remedies against violations of these rights. This paper is based on a desktop and empirical research.